Evaluating Supplementary Irrigation Water Depths for Improving Land and Water Productivity under Grown Tomato in a Semi-Arid Climate, Burkina Faso - Pélagie, Yanogo Wendzoodo Amélie; Sévérin, Kima Aimé; Samuel, Ouoba; Bernice, Sandwidi Béné-Wendé; Etienne, Kima (International Journal of Scientific Research and Management (IJSRM), 2025)
In the actual rainwater variability and the declining water resources context, the great challenge of agriculture in Burkina Faso is to produce more with less water. That may be possible through the optimal use of water in tomato production since the yield is decreasing while the demand is still increasing particularly in the rainy season. Therefore, an experiment was implemented to identify the irrigation water depth that will improve both the yield and the efficiency of water use. The design was a complete randomized block with four replications. Four irrigation water treatments representing 50% (D50%), 75% (D75%), and 100% (D100%) of tomato water requirement were applied. The calculated and adopted irrigation interval was 2 days. After transplanting, a constant water depth (D50%) was used. The water treatments were initiated 15 days after transplanting. The water application was postponed to the next irrigation when the rain occurred. The results showed that the application of D75% increased the tomato yield from 4%. Although microbial activity was inhibited during the first year of experimentation, it increased significantly by 144% compared to the control in the second year. Moreover, results showed that the application of D50% increased the water productivity from 175% compare to full irrigation and appeared profitable. The application of supplementary irrigation of D50% should be adopted in rainfed tomato production for sustainable improvement of lands and water productivity.